Foreign and Domestic Investments as the Economic Growth Determinants in 34 Indonesian Provinces in the 2015-2023 Period - Dyah Putri Sekar Arum; Kaluge, David (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study examines the relationship between Foreign Direct Investment (FDI) and Domestic Investment (DDI) on economic growth in 34 Indonesian provinces, considering other variables as control variables. The research gap lies in the limited understanding of the relative contribution of FDI and DDI to regional economic growth. The purpose of this study is to analyze the effect of both types of investment and the factors that influence the differences in their flows. The method used is panel data analysis with a quantitative causality approach with the population of GRDP, FDI, and FDI of all provinces in Indonesia using saturated sampling. The research findings show that both FDI and FDI have a significant positive influence on economic growth, but the contribution of each varies between provinces. The implication of this study is that it provides insights for policymakers to design more effective investment strategies, by considering local factors that influence investment success.